Case Report: One heart with two lobes: a rare infantile congenital giant left atrial appendage aneurysm - Chan, Yu-Jen; Ly Ly, Nguyen Thi; Hai, Nguyen Minh; Jan, Sheng-Ling (Frontiers in Pediatrics, 2023)
Abstract Left atrial appendage aneurysm (LAAA) is an extremely rare congenital heart abnormality, with varying degrees of symptoms, ranging from asymptomatic to arrhythmia, thromboembolic event or airway obstruction. Most infantile cases were incidentally found by echocardiography. Contrast-enhanced chest tomography can confirm the diagnosis and inform surgical plan. We describe an asymptomatic young female infant who had a unique extreme cardiomegaly on a chest X-ray and received surgical aneurysmectomy. Her heart was restored to a normal cardiac size after the heart surgery.